RUMAH PANGAN LESTARI, PENDAMPINGAN DAN PELAKSANAAN PADA DESA JONGGON KECAMATAN LOA KULU - Sundari, Sundari; Rahmawati, Eka; Damayanti, Arista; Rochyat, Erwin Arief; Syahrani, Syahrani; Drianti, Astik (STAI Darul Qalam Tangerang, 2023)
This Community Service Activity has providing knowledge and assistance in managing Sustainable Food Homes for the people of Jonggon Village in Loa Kulu District, Kutai Kartanegara Regency. Eighty percent (80%) of respondents managed to maintain the continuity of this sustainable food home activity and benefited from this activity and assistance. With the RPL group, it is hoped that this activity can be adopted by other groups so that family food security can be fulfilled through the Sustainable Food Home program. This programmed community service activity provides knowledge in the form of managing sustainable food houses, making compost and processing crops from sustainable food houses